2021
DOI: 10.1039/d0cp05413e
|View full text |Cite
|
Sign up to set email alerts
|

The high power conversion efficiency of a two-dimensional GeSe/AsP van der Waals heterostructure for solar energy cells

Abstract: The van der Waals heterostructure is a practical way to promote the conversion efficiency of solar energy. Here, we demonstrate the efficient performance of the GeSe/AsP heterostructure in solar energy...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 62 publications
1
20
0
Order By: Relevance
“…The PCE of the AsP/WSe 2 heterostructure is as high as 15%, comparable with A S P/MoS 2 (15.5%) and larger than AsP/WS 2 (13%). In addition, the PCE of the AsP/WSe 2 heterostructure is as greater than that as of AsP/CdSe heterostructure (13%), [12] slightly smaller than the GeSe/AsP heterostructure (16%) [66] and phosphorene/MoS 2 (16-18%). [68] The other heterostructures of AsP/MX 2 also have the characteristics of type-II band alignment, wide absorption, a large PCE, and some of them have a built-in electric field.…”
Section: Stabilities and Electronic Properties Of Type-ii Vdw Heteros...mentioning
confidence: 85%
See 3 more Smart Citations
“…The PCE of the AsP/WSe 2 heterostructure is as high as 15%, comparable with A S P/MoS 2 (15.5%) and larger than AsP/WS 2 (13%). In addition, the PCE of the AsP/WSe 2 heterostructure is as greater than that as of AsP/CdSe heterostructure (13%), [12] slightly smaller than the GeSe/AsP heterostructure (16%) [66] and phosphorene/MoS 2 (16-18%). [68] The other heterostructures of AsP/MX 2 also have the characteristics of type-II band alignment, wide absorption, a large PCE, and some of them have a built-in electric field.…”
Section: Stabilities and Electronic Properties Of Type-ii Vdw Heteros...mentioning
confidence: 85%
“…Its E b is slightly larger than GeSe/AsP heterostructure, 0.11 eV. [ 66 ] It means that AsP/WSe 2 AB stacking vdW heterostructure has a small electron–hole recombination probability.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the standard DFT is known to underestimate band gaps which is usually corrected by hybrid functionals [38][39][40][41], Li et al [34] found only a tiny difference (that will not affect the conclusions) between the SBHs calculated using PBE and HSE06. The authors of this study further concluded that PBE-D2 method is able to provide sufficiently reliable results and the HSE06 method is no longer considered in their discussion.…”
Section: Simulation Detailsmentioning
confidence: 99%